THE EFFECT OF GINGER BREWING ON BLOOD PRESSURE IN ELDERLY HYPERTENSION IN TUGUSUMBERJO VILLAGE - Aditya Nuraminudin Aziz; Prawito; Salwa Qowlan Fadhilah (PRIMA WIYATA HEALTH, 2026)
Background: Hypertension in the elderly is caused by changes in blood vessels that increase the risk of cardiovascular disease. Ginger contains gingerol and flavonoids, which can improve blood circulation, helping to lower blood pressure in hypertensive elderly people. Objective: This study aimed to determine the effect of boiled ginger on blood pressure in elderly people with hypertension in Tugusumberjo Village. Methods: This research design used the Quasi-Experimental method with a One-Group Pretest-Posttest design. The sample consisted of 37 respondents determined using the Isaac and Michael formula through a purposive sampling technique. The data collection tool was an observation sheet, and data analysis used the Wilcoxon Test because the data was not normally distributed, so the analysis was carried out with a non-parametric test. Results: This reduction in blood pressure occurs due to the gingerol and flavonoids in ginger, which help dilate blood vessels and improve circulation. With wider blood vessels, blood can flow more smoothly, so the heart doesn't have to work as hard to pump it. Ginger also stimulates the release of the hormone adrenaline, which helps improve blood flow, ultimately helping to lower blood pressure more naturally. Conclusion: Research shows that boiled ginger is effective in lowering blood pressure in elderly people with hypertension. The natural ingredients in ginger support blood vessel health, making this herbal drink worth considering as part of a healthy lifestyle to control blood pressure when consumed regularly.